Suppression of translation during in vitro maturation of pig oocytes despite enhanced formation of cap-binding protein complex eIF4F and 4E-BP1 hyperphosphorylation - Ellederova, Zdenka; Kovarova, Hana; Melo-Sterza, Fabiana; Livingstone, Mark; Tomek, Wolfgang; Kubelka, Michal (Molecular reproduction and development, 2006)
In this study, we document that the overall rate of protein synthesis decreases during in vitro maturation (IVM) of pig oocytes despite enhanced formation of the 5' cap structure eIF4F. Within somatic/interphase cells, formation of the eIF4F protein complex correlates very well with overall rates of protein translation, and the formation of this complex is controlled primarily by the availability of the 5' cap binding protein eIF4E. We show that the eIF4E inhibitory protein, 4E-BP1, becomes phosphorylated during IVM, which results in gradual release of eIF4E from 4E-BP1, as documented by immunoprecipitation analyses. Isoelectric focusing and Western blotting experiments show conclusively that eIF4E becomes gradually phosphorylated with a maximum at metaphase II (M II). The activity of eIF4E and its ability to bind mRNA also increases during oocyte maturation as documented in experiments with m7-methyl GTP-Sepharose, which mimics the cap structure of mRNA. Complementary analysis of flow-through fraction for 4E-BP1, and eIF4G proteins additionally provides evidence for enhanced formation of cap-binding protein complex eIF4F. Altogether, our results bring new insights to the regulation of translation initiation during meiotic division, and more specifically clarify that 4E-BP1 hyper-phosphorylation is not the cause of the observed suppression of overall translation rates.
Keywords: Phosphorylation; Phosphoproteins; fosfoproteiny; down regulace; adaptorové proteiny signální transdukční; proteosyntéza; Protein Biosynthesis; Eukaryotic Initiation Factor-4F; eukaryotický iniciační faktor 4F; Down-Regulation; Swine; Oocytes; ženské pohlaví; zvířata; oocyty; Adaptor Proteins, Signal Transducing; prasata; fosforylace; Female; Animals